Violence and It’s Impact as Seen in Alice Walker’s The Color Purple - Tini Mogea (FKIP, Universitas Palangka Raya, 2022)
This research intends to reveal violence and its impact in Alice Walker’s The Color Purple. The design of this study is qualitative research that pictures the data in the form of words and quotations. The writer collects and selects the data from the primary source, the novel itself, and the secondary source, which includes books explaining research, literature, and some other references that are relevant and support the analysis. In analyzing the data, the writer uses an objective and mimetic approach to explore the literary work as a reflection of human life. The result shows that Afro-American women, as pictured in Celie’s experience, are treated badly physically, sexually, and mentally by black men who are introduced as her stepfather and her husband. These bad treatments are caused by an internal factor that comes from Celie’s plain character: a fear of fighting. Besides that, the external factor, which comes from social conditions at that time, also gives influence toward men’s point of view about black women, in which for them, women are inferior socially so that they are usually the object of cruel treatment from white, even black men.